Bullwhip Effect Study in Leaf Organic Supply Chain - Dwi Apriyani; Rita Nurmalina; Burhanuddin Burhanuddin (Universitas Muhammadiyah Yogyakarta, 2021)
The mismatch between the availability of vegetables and consumer demand is one of the causes of inefficient supply chains. This study aims to analyze the bullwhip effect on the organic leaf vegetable supply chain at PT Simply Fresh Organic (SFO). The analysis method used is a comparison between the coefficient of variation of orders created with the coefficient of variation in requests received by each supply chain institution. The data used are secondary data obtained from PT SFO. The measurement results show that the supply chain flow of organic leaf vegetables had a bullwhip effect at the PT SFO level and no bullwhip effect occurs at the retail level. The value of the BE supply chain value calculation at PT SFO shows a higher figure than at the retail level. The bullwhip effect at PT SFO occurred because of a rationing and shortage gaming policy. Therefore, each member of the supply chain must maintain transparency of data information and utilize digital technology to improve the accuracy of data forecasting requests and reservations quickly.